Associations between weight teasing by peers, self esteem, and academic related stressors with body weight status among adolescents in Hulu Langat district, Selangor, Malaysia - Ibrahim, Nor Mazni; Ibrahim, Zuriati; Jamaluddin, Rosita (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Growing evidence highlighting the physical health risks linked with adolescent obesity and yet little is known on the role of psychosocial factors on the body weight status of adolescents. A cross sectional study was conducted to ascertain the associations between psychosocial factors (operationalised as weight teasing by peers, self-esteem and academic related stressor) with body weight status of adolescents in Hulu Langat District, Selangor, Malaysia. Methods: A total of 455 adolescents aged 13-16 years (50.3% male and 49.7% female) were recruited from five randomly selected schools through a multistage cluster sampling. Body weight and height were assessed and body mass index (BMI) was computed. Weight teasing by peers, self-esteem and academic related stressor were assessed using self-administered questionnaire of Perception of Teasing Scale (POTS), Rosenberg Self esteem Scale (RSE) and Secondary School Stressor (SSS) respectively. Results: The prevalence of overweight and obesity were 17.1% and 12.2%. Binary logistic regression revealed that adolescents who experienced weight teasing by their peers had 12 times higher odds to be overweight and obese. However, low self-esteem and high academic stressor were associated with a reduction in the likelihood of being overweight and obese. This rather contradictory results may be due to various factors that may affect the adolescents’ self-esteem and academic related stressor. Conclusion: Intervention programmes need to consider the peer environment of adolescents, increasing awareness on the effect of weight teasing by peers and further well designed study is crucial to stimulate the central understanding of psychosocial correlates to the adolescent obesity.